Śekha Mujiba ekaṭi lāla golāpa - Manasura, Mināra; Caudhurī, Dilaoẏāra (Epiṭāpha Prakāśanī, 1979)
Commemorative volume on the occasion of the fourth death anniversary of the former Bangladesh president Sheikh Mujibur Rahman, 1922-1975; comprises articles, reminiscences, poems, etc. on his life and activities.